An Indonesian EFL Learner’s Dissertation Writing: Some Problems and Solutions - Anna Marietta da Silva (Journal of English Language and Culture, 2017)
A dissertation is said to be an academician’s peak of academic achievement. One can demonstrate his expertise, passion in a particular field of study, and skills through his dissertation. Yet, in general, writing a dissertation may not be simple for every graduate student, especially when he has to write a dissertation about language in a language that is not his native language, English for instance, indicating that he must be able to show remarkable capabilities in manipulating the language. To find out about how a non-English speaking student coped with any problems persisted during the process of writing his dissertation in English I conducted a brief interview with an Indonesian lecturer, majoring in Linguistics, who wrote his dissertation in English. The interview presented some important fact in relation to successfully producing a qualified dissertation, i.e. mastery of one’s field of study, and the English academic writing skills. Keywords: Dissertation writing, academic writing, linguistics